Method for preparing anthracene derivative - ZHEN YONGGANG; LIU JIE; HU WENPING; BAI HAN; SHU ZHIBIN; DONG HUANLI; JIANG LANG (2017)
The invention discloses a method for preparing an anthracene derivative. The structural formula of the anthracene derivative is formula I shown in the specification. The method comprises the following step: enabling a compound of formula II shown in the specification to react with zinc under an alkali condition, thereby obtaining the anthracene derivative of formula I shown in the specification. By adopting the method, the defects that a conventional synthesis method is low in raw material availability, high in price, high in production equipment requirement, high in safety and environment protection pressure and unbeneficial to industrial production are overcome. The method has the advantages of being simple, efficient, environmentally friendly, low in raw material price, and low in reagent use amount; raw materials, reagents and solvents are not highly required and can be only chemically pure; the method is high in universality and repeatability. 本发明公开了种蒽衍生物的制备方法。所述蒽衍生物的结构式如式Ⅰ所示，其制备方法包括下述步骤：使式Ⅱ所示化合物与锌在碱性条件下